On the chromaticity of complete multipartite graphs with certain edges added - Lau, G. C.; Peng, Y. H. (Elsevier, 2008)
Let P.G; / be the chromatic polynomial of a graph G. A graph G is chromatically unique if for any graph H, P.H; / D P.G; / implies H is isomorphic to G. For integers k 0, t 2,denote by K..t